2017
DOI: 10.1007/s10461-017-1856-9
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Factors Associated With Painful Versus Non-Painful HIV-Associated Sensory Neuropathy

Abstract: HIV-associated sensory neuropathy (HIV-SN) is a common, and frequently painful complication of HIV, but factors that determine the presence of pain are unresolved. We investigated: (i) if psychological factors associated with painful (n = 125) versus non-painful HIV-SN (n = 72), and (ii) if pain and psychological factors affected quality of life (QoL). We assessed anxiety and depression using the Hopkins Symptoms Checklist-25. Pain catastrophizing and QoL were assessed using the Pain Catastrophizing Scale and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 53 publications
0
23
0
Order By: Relevance
“…We report that the incidence of SN on TDF‐based cART, based on clinical evaluation, is lower than that observed on stavudine‐based therapies, and that it is more frequently asymptomatic. Nevertheless, a percentage of individuals developed a rapid onset symptomatic neuropathy, which might lead to disability and reduced quality of life . Concomitant active TB disease increased the risk of developing SN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We report that the incidence of SN on TDF‐based cART, based on clinical evaluation, is lower than that observed on stavudine‐based therapies, and that it is more frequently asymptomatic. Nevertheless, a percentage of individuals developed a rapid onset symptomatic neuropathy, which might lead to disability and reduced quality of life . Concomitant active TB disease increased the risk of developing SN.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, a percentage of individuals developed a rapid onset symptomatic neuropathy, which might lead to disability and reduced quality of life. 42 Concomitant active TB disease increased the risk of developing SN. Our findings suggest that SN continues to be a clinical problem in low-income countries where prevalence of comorbid TB and HIV remains high.…”
Section: Discussionmentioning
confidence: 99%
“…In a more recent study, Adoukonou et al revealed the presence of pain in 23.4% of patients [7], while other studies report painful symptoms in up to 75% of HIV-SN participants [8]. Pain is associated with depression and poor quality of life [1,[9][10][11]. Depression seems to be associated with greater pain intensity [1,12].…”
Section: Introductionmentioning
confidence: 96%
“…Among the broad spectrum of HIV infection symptoms, HIV sensory neuropathy (HIV-SN) remains one of the main causes of suffering, having subsequent impact on quality of life of these patients [1]. It has been estimated that up to one-third of HIV infected individuals suffer from HIV-SN [2], with incidence varying from 13% to up to 50% [3,4], primarily due to different diagnostic criteria [2,3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation